Automating the test case generation for Object Oriented Systems using Activity Diagrams (International Journal of Engineering and Computer Science, 2015)
Generation of test cases is the most important issue in the software testing. Thus test cases need to be carefully designed. An activity diagram is used for modelling the dynamic aspects of the system. It helps in visualizing the sequence of activities involved in a control flow. The proposed approach is to automate the generation of test scenarios from activity diagram using DFS and BFS method. By using these two methods, the useless test paths are eliminated which in turn reduces the time complexity. This approach also helps in synchronization between various activities. It generates an Activity Graph from the activity diagram by specifying some mapping rules. Then a proposed approach will generate the number of valid paths by using activity graph as an input and these valid paths will help in generating the test cases which will cover all aspects of the system and results in increased system efficiency and performance.